Is there a biomechanically efficient vertical ground reaction force profile for countermovement jumps? - McHugh, M. P.; Hickok, M.; Cohen, J. A.; Virgile, A.; Connolly, D. A. J. (Translational Sports Medicine, 2021)
The purpose of this study was to determine whether countermovement jump (CMJ) metrics differed based on whether or not peak vertical ground reaction force (GRF) occurred at the lowest point of the countermovement (low position). CMJs from 100 athletes were categorized based on whether or not the peak force occurred at low position and whether they had unimodal or bimodal GRF profiles. CMJ metrics were compared between jump categories and between athletes with above average, average, and below average jump heights. Peak force occurred at low position in 52% of jumps. The majority of jumps were bimodal (78%) and in 73% of bimodal jumps the first peak was higher than the second peak. Both performance metrics (5% higher jump, 25% greater reactive strength index) and most braking phase metrics were superior for jumps in which peak force coincided with low position (P < .01). Peak force occurred at low position in 76% of above average jumps, 50% of average jumps, and 37% of below average jumps (P = .019). The optimal profile for CMJ performance is one in which peak force occurs at low position, regardless of whether it is unimodal or bimodal. This provides a qualitative means of identifying biomechanically efficient jumps